Sing aloud harmonious spheres
1 online resource (xii, 294 pages)
Keywords: This is the first volume to explore the reception of the Pythagorean doctrine of cosmic harmony within a variety of contexts, ranging chronologically from Plato to 18th-century England. This original collection of essays engages with contemporary debates concerning the relationship between music, philosophy, and science, and challenges the view that Renaissance discussions on cosmic harmony are either mere repetitions of ancient music theory or pre-figurations of the 'Scientific Revolution'. Utilizing this interdisciplinary approach, Renaissance Conceptions of Cosmic Harmony offers a new perspective on the reception of an important classical theme in various cultural, sequential and geographical contexts, underlying the continuities and changes between Antiquity, the Middle Ages and the Renaissance. This project will be of particular interest within these emerging disciplines as they continue to explore the ideological significance of the various ways in which we appropriate the past.